2008
DOI: 10.1557/jmr.2008.0147
|View full text |Cite
|
Sign up to set email alerts
|

Fast assembly of bio-inspired nanocomposite films

Abstract: This paper presents a spin-coating layer-by-layer assembly process to prepare multilayered polyelectrolyte-clay nanocomposites. This method allows for the fast production of films with controlled layered structure. The preparation of a 100-bilayer film with a thickness of about 330 nm needs less than 1 h, which is 20 times faster than conventional dip-coating processes maintaining the same hardness and modulus values. For validation of this technique, nanocomposite films with thicknesses up to 0.5 m have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…The film growth was nearly 100× faster when compared to linear LBL. In the second case, spin-assisted LBL was recently used by Vertlib et al for accelerating assembly of PDDA/Laponite composites [74]. The authors found that the mechanical properties of the resulting films were approaching those obtained from dip-coating LBL, with H ≈ 0.44 GPa and E ≈ 8 GPa, yet with 10× faster deposition speed.…”
Section: Clay Multilayers As High-performance Nanocompositesmentioning
confidence: 99%
“…The film growth was nearly 100× faster when compared to linear LBL. In the second case, spin-assisted LBL was recently used by Vertlib et al for accelerating assembly of PDDA/Laponite composites [74]. The authors found that the mechanical properties of the resulting films were approaching those obtained from dip-coating LBL, with H ≈ 0.44 GPa and E ≈ 8 GPa, yet with 10× faster deposition speed.…”
Section: Clay Multilayers As High-performance Nanocompositesmentioning
confidence: 99%
“…[1][2][3][4] The cleverly layered micro/nanostructure, usually called "brick and mortar", has been considered to be the primary reason for the incredibly increase in toughness. [ 5,6 ] In the last decades, numerous nacre-like materials showing excellent mechanical properties [ 7,8 ] have been synthesized by constructing binary layered structures with an inorganic and organic matrix through layer-by-layer deposition, [ 9 ] vacuum assisted fi ltration, [ 10 ] evaporation, [ 11 ] dip coating, [ 12 ] and freeze casting. [ 13,14 ] Different inorganic building blocks such as nanoclays, [ 15,16 ] Al 2 O 3 fl akes, [ 17,18 ] CaCO 3 plates, [ 19,20 ] layered double hydroxides, [ 21 ] fl attened double-walled carbon nanotubes, [ 22 ] and graphene/graphene oxide sheets, [23][24][25] and various organic matrices including natural proteins [ 26 ] and man-made polymers, such as PVA [ 27 ] and PMMA, [ 28 ] have been adopted to further improve the mechanical properties.…”
mentioning
confidence: 99%
“…The spin-coating LbL assembly methodology is a faster alternative to the dip-coating technique. The build up of a 100-bilayer multilayered polyelectrolyte clay film with a thickness of ∼330 nm needs <1 h, which is 20 times faster than dip-coating processes with the same characteristics [79].…”
Section: Layer-by-layer and Spin-coating Methodologiesmentioning
confidence: 99%